High Seroprevalence of Antibodies against Arboviruses among Pregnant Women in Rural Caribbean Colombia in the Context of the Zika Virus Epidemic (2020)
Mosquito-borne viruses such as dengue (DENV), chikungunya (CHIKV), and Zika (ZIKV) have spread in recent decades. We aimed to assess seroprevalence of arboviral infections in pregnant women living in Cereté, Caribbean Colombia. In 2016 a cross-sectional facility-based sero-survey study was performed among pregnant women (N = 90). Most of them (66%) reported at least one symptom or sign compatible with arboviral infection over the previous 15 days. All screened women had a positive IgG for DENV, 89% for ZIKV, and 82% for CHIKV. One woman tested positive for ZIKV IgM. This study shows the high exposure among pregnant women to arboviruses in endemic areas, shown by the high seroprevalence of past arboviral infections. Given the evidence on the potential risks of these arboviral infections on pregnancy and infant outcomes, these results highlight the need for continuous epidemiological surveillance of arboviral diseases, particularly among those most of risk of their harmful consequences.